Development of Extrudable Hydrogels Based on Carboxymethyl Cellulose–Gelatin Complex Coacervates - Hamid Gharanjig; Hossein Najaf Zadeh; Campbell Stevens; Pram Abhayawardhana; Tim Huber; Ali Reza Nazmi (Gels)
This study investigates the 3D extrusion printing of a carboxymethyl cellulose (CMC)–gelatin complex coacervate system. Various CMC–gelatin coacervate hydrogels were prepared and analyzed to achieve this goal. The impact of the CMC–gelatin ratio, pH, and total biopolymer concentration on coacervation formation and rheological properties was evaluated to characterize the printability of the samples. Turbidity results indicated that the molecular interactions between gelatin and CMC biopolymers are significantly pH-dependent, occurring within the range of pH 3.7 to pH 5.6 for the tested compositions. Confocal Laser Scanning Microscopy (CLSM) confirmed the presence of coacervates as spherical particles within the optimal coacervation range. Scanning electron microscopy micrographs supported the CLSM findings, revealing greater porosity within this optimal pH range. Rheological characterization demonstrated that all CMC–gelatin hydrogels exhibited pseudoplastic behavior, with an inverse correlation between increased coacervation and decreased shear viscosity. Additionally, the coacervates displayed lower tackiness compared to gelatin hydrogels, with the maximum tackiness normal force for various CMC–gelatin ratios ranging from 1 to 15 N, notably lower than the 29 N observed for gelatin hydrogels. Mixtures with CMC–gelatin ratios of 1:15 and 1:20 exhibited the best shear recovery behavior, maintaining higher strength after shear load. The maximum strength of the CMC–gelatin coacervate system was found at a biopolymer concentration of 6%. However, lower biopolymer content allowed for consistent extrusion. Importantly, all tested samples were successfully extruded at 22 ± 2 °C, with the 1:15 biopolymer ratio yielding the most consistent printed quality. Our research highlights the promise of the CMC–gelatin coacervate system for 3D printing applications, particularly in areas that demand precise material deposition and adjustable properties.